Enhancing Accountability in Schools : What Can Choice and Contracting Contribute - Patrinos, Harry Anthony; LaRocque, Norman (World Bank, Washington, DC, 2012)
This note claims that contracting in education can be employed for initiatives of varying sizes and across a range of services. For policy-makers, contracting represents an effective means of introducing accountability in the education system. Contracting can also insulate governments from some of the criticism leveled at privatization. Moreover, it can bring in skills and capital to the education sector.